Hubungan Kepatuhan Melaksanakan Manajemen Diabetes Melitus denganKualitas Hidup Penderita Diabetes Melitus di Puskesmas Haurpanggung Garut - Sulastini; Esa Risi Suazini; Rindiani; Bambang Aditya Nugraha (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction :Diabetes Mellitus (DM) is a chronic disease characterized by high blood glucose levels that exceed normal limits. People with diabetes require special care throughout   their   lives,   which   is   called   diabetes   management.   Diabetes management aims to stabilize blood glucose levels and prevent complications. Quality of life is a person's perception or view of the life he lives. Objective: The purpose of this study was to determine the relationship between adherence to diabetes management and the quality of life of people with diabetes mellitus. Methode: This type of research is a quantitative study with a research design using a cross sectional method with a total sample of 30 respondents. Sample selection using purposive sampling technique. Data collection tools are questionnaires, for compliance with DM management using the DSMQ (Diabetes Self-Management Questionnaire) questionnaire and quality of life using the WHOQOL-BREF questionnaire. Result: Data analysis using Spearman Rank analysis. The results obtained p-value 0.007 (p<0.05). Conclusion: so it can be concluded that there is a relationship between adherence to diabetes management and the quality of life of diabetics. The results of this study are expected to be additional material to improve compliance with DM management